DESIGN AND DEVELOPMENT OF A STEALTH UNIC FOR SILENT OPERATION WITH ESP32-BASED AUTONOMOUS CONTROL - Nur Rachman Supadmana Muda; Hasby Fajrus Shodiq (Bajang Institute, 2024)
This research aims to design and build a stealth kamikaze drone for Silent Operation, named Unic, with an autonomous control system. In a modern context that increasingly emphasizes military technology, the existence of drones capable of conducting precision attacks without detection has become essential. This drone is designed to target enemy objectives with the aim of effectively detonating targets without being detected. The design process includes the selection of key components using ESP32, the development of autonomous navigation algorithms, and the integration of secure communication systems. In terms of stealth, the drone is equipped with silent-designed brushless motors that produce noise levels below 25 dB to reduce the likelihood of being heard from a distance. This research also includes performance testing of the drone in simulated scenarios, focusing on maneuverability, navigation accuracy, and stealth capabilities to avoid radar detection and other surveillance systems. Test results show that Unic can perform autonomous flights with high accuracy, optimizing stealth to evade radar and sound detection. These findings are expected to contribute to the development of military drone technology and enhance the effectiveness of national defense strategies. Future research will focus on improving sensor capabilities and anti-jamming systems to support operations in complex environments.